Prevalence and pattern of overweight and obesity in three rural communities in southwest Nigeria - Adebayo RA (Dove Medical Press, 2014)
Rasaaq A Adebayo,1 Michael O Balogun,1 Rufus A Adedoyin,2 Oluwayemisi A Obashoro-John,3 Luqman A Bisiriyu,4 Olugbenga O Abiodun11Department of Medicine, 2Department of Medical Rehabilitation, Obafemi Awolowo University, Ile-Ife, 3Department of Adult Education, University of Lagos, Lagos, 4Department of Demography and Social Statistics, Obafemi Awolowo University, Ile-Ife, NigeriaBackground: Limited data exist on the prevalence of overweight and obesity in the Nigerian adult rural population. This study therefore assessed the prevalence and pattern of overweight and obesity in adults in three rural communities of the Ife North Local Government Area, Nigeria.Materials and methods: A total of 777 adults between 20 and 90 years of age were recruited into this cross-sectional study, which was performed over a 6-month period using a multistage proportional stratified random sampling technique. Sociodemographic data and anthropometric variables were obtained.Results: A total of 385 (49.5%) men and 395 (50.5%) women participated in the study. The mean age and body mass index of the participants were 36.3±14.3 years and 23.53±4.6 kg/m2, respectively. The overall crude prevalence of overweight and obesity in the total population were 20.8% and 8.4%, respectively. Obesity increased across the age gradient, peaking in the 51- to 60-year age-group in men and women. Among the overweight and obese subjects (n=227), 70.9% of them were overweight and the remaining 29.1% were obese, with class I obesity accounting for 20.7% of these overweight and obese subjects.Conclusion: The prevalence of overweight and obesity in these communities was 20.8% and 8.4% respectively, indicating a trend towards increased prevalence. Class I obesity is the most common obesity pattern, and obesity increased across the age gradient, peaking in the 51- to 60-year age-group. There is a need for regular community education on healthy lifestyles, and regular health screening to control the rising prevalence of overweight and obesity, as well as to prevent or reduce the risk of obesity comorbidities in these communities.Keywords: obesity, prevalence, rural, communities, Osun State, Nigeria